Kura'an-ı kerim'de kutsama terimi - Laksono, Bagus (İstanbul Sabahattin Zaim Üniversitesi, 2021)
Allah'ın rızkı idare etme kudretinin delillerinden biri de rızkın insanlar arasında bol veya az olmasına şahit olmamızdır. Rızık edinme, sadece onu arama yeteneği ile değil, birbiriyle ilişkili birçok faktör tarafından belirlenir ve hepsi Allah (cc)'ın kontrolü altındadır. Ve başlangıçta insanın hiçbir şeyi yoktur, sonra Allah ona nimet verir, fakat Allah her insana nimet vermez ve gerçekten o, inanan ve takva sahibi insanlara nimet verir. Ve Allah (cc), Kuran'da bildirdiği gibi, inanan ve takva sahibi kimselere nimetler vaat etmiştir. Bu araştırma bir literatür çalışması olduğundan, araştırmacı bulduğu kitaplardan bilgi toplamak için yazılı belgeler kullanır. Bu çalışma tümevarımsal ve analitik bir yaklaşımı bir araya getirmektedir. Çünkü araştırmacı Kuran'ın ayetlerinde geçen nimet kavramını anlamakla ilgilenmektedir. Bu çalışmanın amaçlarından birincisi, Kuran'daki nimet kavramını anlamak, ikincisi: Kuran'ın nimet kelimesi için kullanılması, üçüncüsü: Kuran'da belirtildiği gibi nimetleri aramada ve anlamada ılımlılık ve dördüncü: nimetlerin elde edilmesini garanti eden genel kurallar. Çalışmanın sonuçlarına göre, nimetler, fayda sağlayan iyiliklerin tümüdür. Kur'an'ın rehberliğinde bir kimse hem dünyada hem de ahirette nimetlere kavuşur. Eğer bir kimse Allah'a ve Resulüne, inanırsa ve Allah'tan ve onun resulünden korkarsa, Allah, gökten bereket kapısını, yani yağmur suyu formunda ve yerden bereket kapısını, yani bereketli toprak ve bitki yetiştirme şeklinde açar ve o itaat ve ibâdete devam edebilmek için, nimet istemede ölçülü olmalı, nimet aramada aşırılık ve gaflet etmemelidir.

Signs of God's power in the regulation of sustenance, among others, the appearance of a person's sustenance a lot or less. The acquisition of sustenance is not only determined by the ability to seek it, but also by the many interrelated factors and all of them are under the control of Allah swt. And in the beginning a person has nothing, then Allah gives blessings to him, but Allah does not give blessings to every human being, and indeed he gives blessings to people who believe and are pious. And Allah SWT has promised blessings for those who believe and are pious. And Allah swt has made blessing as a very great blessing, through which one can obtain the benefits of the world and the benefits of religion that transcend the boundaries of space, time, and human consciousness. Therefore, obtaining blessings is an intended purpose for the work to have its effect, and its benefits will remain in the next generation. Based on the above Facts, it is our obligation to re-learn the understanding of blessings and know their concepts and truths in the Qur'an. Because this research is a literature study, the researcher uses written documents to collect information from the books found by the researcher. This study combines an inductive and analytical approach because the researcher is interested in understanding the term blessing in the verses of the Qur'an. The objectives of this study are, first: understanding the term blessing in the Qur'an, second: the use of the Qur'an for the word blessing, third: moderation in understanding and seeking blessings as indicated in the Qur'an, and fourth: general rules that guarantee the achievement of blessings. Based on the results of the study, blessings are all actions in goodness that cause benefits. If someone is guided by the Qur'an, he will get blessings both in this world and in the hereafter. And if a person believes and fears Allah and His Messenger, Allah will open the door of blessing from the sky, namely in the form of rainwater and blessings from the earth, namely fertile soil and growing plants, and he should be moderate in asking for blessings, and not be excessive or negligent in seeking blessing so that one can continue in obedience and in worship.
Keywords: Din; Religion; Hazinetü`l-Esrar ve Ganimetü`l-Ebrar; Hazinetü`l-Esrar ve Ganimetü`l-Ebrar